Preliminary findings of the distribution of alpha-2-adrenergic receptor (ADRA2A) rs1800544 polymorphisms in kickboxing players - TACAL ASLAN, BESTE; OKTAY, NİHAL ŞEHKAR; ULUCAN, KORKUT (My University, 2021)
Objective: Adrenergic receptors play an important role in providing neurotransmitter release from the sympathetic nervous system and adrenergic neurons. The rs1800544 polymorphism in 3’-untranslated region of Alpha-2-Adrenergic Receptor (ADRA2A) is if caused by C>G tranversion at position –1291. In this study, we objective to analyze the rs1800544 distribution in kickboxing players. Methods: A total of 12 male players and 101 sedentary individuals (as a control group) participated in the study. Following DNA isolation, rs1800544 polymorphism of ADRA2A gene was determined by real-time polymerase chain reaction (Rt-PCR). Statistical analysis was carried out by chi-square test. Results: CC, CG and GG genotypes and percentages for rs1800544 polymorphism were analyzed as 5 (41,7%), 4 (33,3%) and 3 (25%), respectively. C allele was counted as 14 (58,3%) and G allele as 10 (41,7%). In the control group CC, CG and GG were found as 34 (33,6%), 53 (52,5%), 14(13,9%), respectively. C allele was counted as 121 (60%) and G allele as 81 (40%). When we compare athletes and controls in the terms of genotypes, we detected no statistically significant difference (p>0,3940). For the allele comparison, we detected no significant difference between groups (p>0,0871). Conclusion: Determination of gene combinations in athletes is of great importance for determination of the effect of genetic factors in athletic performance. In our cohort, CC genotype was more frequently found, and C allele was also higher in players. We think that the effect of ADR2A2 gene on athletic performance might be determined more clearly by the fact that this study is an example of similar studies involving higher numbers of subjects.
Keywords: TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); ADRA2A; Polymorphism; Sports; Kickboxing players; GENE; ADRA2A; Polymorphism; Sports; Kickboxing players